Hexahelix Strategy to Reduce ICOR by Enhancing Investment, Bureaucracy, and Eradicating Corruption - Ajeep Akbar Qolby; M. Alvi Syahrin; Koesmoyo Ponco Aji (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The problem of low investment efficiency in Indonesia as reflected by the high Incremental Capital Output Ratio (ICOR) value. The condition is exacerbated by corrupt practices, inefficient bureaucracy, declining labor productivity, and inadequate immigration governance, which overall hamper economic growth. Through historical analysis and empirical data, this essay identifies the important role of various elements government, industry sector, society, academia, mass media, and the legal and regulatory system in creating a conducive investment climate. As a strategic solution, the author proposes the HEXAHELIX collaborative model, which is a development of the Triple and Quadruple Helix concepts, to improve investment quality, reduce corrupt practices, reform immigration policies, and optimize capital utilization. This model emphasizes the need for synergy between various stakeholders to realize bureaucratic and immigration reform, transparency in investment management, and equitable development between regions. Thus, the implementation of the HEXAHELIX collaborative strategy is expected to reduce the ICOR rate, increase productivity, and encourage inclusive and sustainable economic growth, while realizing political stability and community welfare.